Physiological intracranial calcification in Eastern Indian population-A CT scan study - Panchali Som; Rajarshi Roy; Sumit Datta; Asis Kumar Ghosal; Anubha Saha; Subhajit Halder (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Knowledge of physiological calcification in brain parenchyma is essential to avoid misinterpretation during radiological evaluation. The calcifications are commonly seen in pineal gland, falx cerebri, tentorium cerebelli and choroid plexus. Objective: To determine the incidence of physiological intracranial calcification and its relationship to age and sex in eastern Indian population. Materials and Method: A cross sectional descriptive study of CT scan brain was performed in age group between 20-80 yrs in eastern India. The study was conducted on 64 Slice MDCT PHILIPS Brilliance. Bulk of our patients was of road traffic accidents and routine CT scan study revealed these physiological calcifications and did not possess any morphological abnormality.Results: 852 patients of which 503 male and 349 female were studied and overall 1429 separate calcified areas were identified due to co-existent calcifications in most of the patients. The incidence of calcification was in pineal gland (62%), choroid plexus (53%), dura mater (26%), basal ganglia (2.8%), dentate nucleus (1.4%) and Habenular nuclei (6%). Incidence is more in male than in female. Conclusion: Physiological calcifications in some of the intracranial structures are not a very uncommon finding and it should not be confused with a pathological one.